An Assessment of Students’ Satisfaction Level from Learning Management Systems: Case Study of Payamnoor and Farhangian Universities - Shayan, P.; Iscioglu, E. (Engineering, Technology & Applied Science Research, 2017)
Learning Management Systems (LMS) have played a significant role in education. The purpose of this study is to investigate the acceptance level of LMS amongst students of two Universities in Tehran, Payamnoor and Farhangian. The total number of participants was 200. This study was directed based on a quantitative research method and data collection from a questionnaire which was then interpreted according to accurate statistical procedures through SPSS software. Results show that most students, regardless their gender, age, and department were satisfied with the usage of Payamnoor and Farhangian LMSs. However, a student’s grades seem to play a significant role regarding his or hers level of satisfaction from the LMS.